Pengembangan Media Pembelajaran Berbasis Plotagon Dan Wordwall Pada Materi Aliran-Aliran Ilmu Kalam Kelas XI Di MA Darul Ulum Palangka Raya - Odah, Raudah; Ansyari, Ridho; Amanda, Raihanah; Azis, Abdul (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to make interactive learning by using plotagon applications and wordwall-based evaluation games to make learning more active in order to avoid monotonous learning that results in boredom. Therefore, this study uses Research and Develompment (R&D) research. Development of learning media using ADDIE model with stages, namely, Analysis, Design, Deveploment, Implementation, Evaluations. Instruments used to collect data through questionnaires (likert scale) at the time of the trial. The results of the expert assessment of the material with a very good category while the results of the expert assessment of the media with a very good category. The results of the assessment of learning media at the implementation stage by educators reached a very good category, as well as the results of the assessment of the response of students to the feasibility of Learning media and materials presented have a very good category. Based on the results of research conducted, it can be concluded that the learning media using plotagon and wordwall is feasible to use in the eyes of the Class XI ahlak Creed on the subject of Kalam streams.